Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Incidence of farrowing assistance and neonatal challenges in hyperprolific sows: Insights from a field study - S. Blim; D. Lehn; T. Scheu; C. Koch; G. Thaller; K. Failing; H. Bostedt (Theriogenology, 2026)

The role of submarine volcanism in atmospheric chemistry - M. Colombier; M. Bonifacie; M. Brenna; A. Burke; C. Cimarelli; S.J. Cronin; P. Delmelle; D.B. Dingwell; K-U. Hess; M. Huebsch; T. Kula; F. Latu’ila; et al. (Earth and Planetary Science Letters, 2025)

The rheology of rhyolite magma from the IDDP-1 borehole and Hrafntinnuhryggur (Krafla, Iceland) with implications for geothermal drilling - Fabian B. Wadsworth; Jérémie Vasseur; Yan Lavallée; Kai-Uwe Hess; Jackie E. Kendrick; Jonathan M. Castro; Daniel Weidendorfer; Shane M. Rooyakkers; Annabelle Foster; Lucy E. Jackson; Ben M. Kennedy; Alexander R.L. Nichols; et al. (Journal of Volcanology and Geothermal Research, 2024)

Species delimitation 4.0: integrative taxonomy meets artificial intelligence - Kevin Karbstein; Lara Kösters; Ladislav Hodač; Martin Hofmann; Elvira Hörandl; Salvatore Tomasello; Natascha D. Wagner; Brent C. Emerson; Dirk C. Albach; Stefan Scheu; Sven Bradler; Jan de Vries; et al. (Trends in Ecology & Evolution, 2024)

Three perspectives on the prediction of chemical effects in ecosystems - Anke Schneeweiss; Noël P. D. Juvigny‐Khenafou; Stephen Osakpolor; Andreas Scharmüller; Sebastian Scheu; Verena C. Schreiner; Roman Ashauer; Beate I. Escher; Florian Leese; Ralf B. Schäfer (Global Change Biology, 2023)
The increasing production, use and emission of synthetic chemicals into the environment represents a major driver of global change. The large number of synthetic chemicals, limited knowledge on exposure patterns and effects in organisms and their interaction with other global change drivers hamper the prediction of effects in ecosystems. However, recent advances in biomolecular and computational methods are promising to improve our capacity for prediction. We delineate three idealised perspectives for the prediction of chemical effects: the suborganismal, organismal and ecological perspective, which are currently largely separated. Each of the outlined perspectives includes essential and complementary theories and tools for prediction but captures only part of the phenomenon of chemical effects. Links between the perspectives may foster predictive modelling of chemical effects in ecosystems and extrapolation between species. A major challenge for the linkage is the lack of data sets simultaneously covering different levels of biological organisation (here referred to as biological levels) as well as varying temporal and spatial scales. Synthesising the three perspectives, some central aspects and associated types of data seem particularly necessary to improve prediction. First, suborganism‐ and organism‐level responses to chemicals need to be recorded and tested for relationships with chemical groups and organism traits. Second, metrics that are measurable at many biological levels, such as energy, need to be scrutinised for their potential to integrate across levels. Third, experimental data on the simultaneous response over multiple biological levels and spatiotemporal scales are required. These could be collected in nested and interconnected micro‐ and mesocosm experiments. Lastly, prioritisation of processes involved in the prediction framework needs to find a balance between simplification and capturing the essential complexity of a system. For example, in some cases, eco‐evolutionary dynamics and interactions may need stronger consideration. Prediction needs to move from a static to a real‐world eco‐evolutionary view.

Magma fragmentation: a perspective on emerging topics and future directions - Thomas J. Jones; Katharine V. Cashman; Emma J. Liu; Alison C. Rust; Bettina Scheu (Bulletin of Volcanology, 2022)
The breaking apart of magma into fragments is intimately related to the eruptive style and thus the nature and footprint of volcanic hazards. The size and shape distributions of the fragments, in turn, affect the efficiency of heat transfer within pyroclastic plumes and currents and the settling velocity, and so the residence time, of particles in the atmosphere. Fundamental work relating the glass transition to the fragmentation of magmas remains at the heart of conceptual and numerical models of volcanic eruptions. Current fragmentation criteria, however, do not predict the sizes and shapes of the resulting fragments, or fully account for the multiphase nature of magmas or ways in which magma can break in a fluidal manner or by thermal stress. The pulsatory, non-steady state nature of some eruptions, and related interactions with these fragmentation criteria, also requires further investigation. Here, we briefly review some recent advances in the field of magma fragmentation and provide a perspective on how integrated field, experimental and numerical modelling studies can address key outstanding challenges.

In situ observation of the percolation threshold in multiphase magma analogues - M. Colombier; F. B. Wadsworth; B. Scheu; J. Vasseur; K. J. Dobson; F. Cáceres; A. Allabar; F. Marone; C. M. Schlepütz; D. B. Dingwell (Bulletin of Volcanology, 2020)
Magmas vesiculate during ascent, producing complex interconnected pore networks, which can act as outgassing pathways and then deflate or compact to volcanic plugs. Similarly, in-conduit fragmentation events during dome-forming eruptions create open systems transiently, before welding causes pore sealing. The percolation threshold is the first-order transition between closed- and open-system degassing dynamics. Here, we use time-resolved, synchrotron-source X-ray tomography to image synthetic magmas that go through cycles of opening and closing, to constrain the percolation threshold Φ C at a range of melt crystallinity, viscosity and overpressure pertinent to shallow magma ascent. During vesiculation, we observed different percolative regimes for the same initial bulk crystallinity depending on melt viscosity and gas overpressure. At high viscosity (> 10 6 Pa s) and high overpressure (~ 1–4 MPa), we found that a brittle-viscous regime dominates in which brittle rupture allows system-spanning coalescence at a low percolation threshold ( Φ C ~0.17) via the formation of fracture-like bubble chains. Percolation was followed by outgassing and bubble collapse causing densification and isolation of the bubble network, resulting in a hysteresis in the evolution of connectivity with porosity. At low melt viscosity and overpressure, we observed a viscous regime with much higher percolation threshold ( Φ C > 0.37) due to spherical bubble growth and lower degree of crystal connection. Finally, our results also show that sintering of crystal-free and crystal-bearing magma analogues is characterised by low percolation thresholds ( Φ C = 0.04 – 0.10). We conclude that the presence of crystals lowers the percolation threshold during vesiculation and may promote outgassing in shallow, crystal-rich magma at initial stages of Vulcanian and Strombolian eruptions.

MeMoVolc report on classification and dynamics of volcanic explosive eruptions - C. Bonadonna; R. Cioni; A. Costa; T. Druitt; J. Phillips; L. Pioli; D. Andronico; A. Harris; S. Scollo; O. Bachmann; G. Bagheri; S. Biass; et al. (Bulletin of Volcanology, 2016)

Unifying elemental stoichiometry and metabolic theory in predicting species abundances - David Ott; Christoph Digel; Björn C. Rall; Mark Maraun; Stefan Scheu; Ulrich Brose (Ecology Letters, 2014)
While metabolic theory predicts variance in population density within communities depending on population average body masses, the ecological stoichiometry concept relates density variation across communities to varying resource stoichiometry. Using a data set including biomass densities of 4959 populations of soil invertebrates across 48 forest sites we combined these two frameworks. We analyzed how the scaling of biomass densities with population‐averaged body masses systematically interacts with stoichiometric variables. Simplified analyses employing either only body masses or only resource stoichiometry are highly context sensitive and yield variable and often misleading results. Our findings provide strong evidence that analyses of ecological state variables should integrate allometric and stoichiometric variables to explain deviations from predicted allometric scaling and avoid erroneous conclusions. In consequence, our study provides an important step towards unifying two prominent ecological theories, metabolic theory and ecological stoichiometry.

Mechanisms linking plant community properties to soil aggregate stability in an experimental grassland plant diversity gradient - G. Pérès; D. Cluzeau; S. Menasseri; J. F. Soussana; H. Bessler; C. Engels; M. Habekost; G. Gleixner; A. Weigelt; W. W. Weisser; S. Scheu; N. Eisenhauer (Plant and Soil, 2013)

A comparison of the strength of biodiversity effects across multiple functions - Eric Allan; Wolfgang W. Weisser; Markus Fischer; Ernst-Detlef Schulze; Alexandra Weigelt; Christiane Roscher; Jussi Baade; Romain L. Barnard; Holger Beßler; Nina Buchmann; Anne Ebeling; Nico Eisenhauer; et al. (Oecologia, 2013)

Soil organisms shape the competition between grassland plant species - Alexander C. W. Sabais; Nico Eisenhauer; Stephan König; Carsten Renker; François Buscot; Stefan Scheu (Oecologia, 2012)

Divergent composition but similar function of soil food webs of individual plants: plant species and community effects - T. M. Bezemer; M. T. Fountain; J. M. Barea; S. Christensen; S. C. Dekker; H. Duyts; R. van Hal; J. A. Harvey; K. Hedlund; M. Maraun; J. Mikola; A. G. Mladenov; et al. (Ecology, 2010)
Soils are extremely rich in biodiversity, and soil organisms play pivotal roles in supporting terrestrial life, but the role that individual plants and plant communities play in influencing the diversity and functioning of soil food webs remains highly debated. Plants, as primary producers and providers of resources to the soil food web, are of vital importance for the composition, structure, and functioning of soil communities. However, whether natural soil food webs that are completely open to immigration and emigration differ underneath individual plants remains unknown. In a biodiversity restoration experiment we first compared the soil nematode communities of 228 individual plants belonging to eight herbaceous species. We included grass, leguminous, and non‐leguminous species. Each individual plant grew intermingled with other species, but all plant species had a different nematode community. Moreover, nematode communities were more similar when plant individuals were growing in the same as compared to different plant communities, and these effects were most apparent for the groups of bacterivorous, carnivorous, and omnivorous nematodes. Subsequently, we analyzed the composition, structure, and functioning of the complete soil food webs of 58 individual plants, belonging to two of the plant species, Lotus corniculatus (Fabaceae) and Plantago lanceolata (Plantaginaceae). We isolated and identified more than 150 taxa/groups of soil organisms. The soil community composition and structure of the entire food webs were influenced both by the species identity of the plant individual and the surrounding plant community. Unexpectedly, plant identity had the strongest effects on decomposing soil organisms, widely believed to be generalist feeders. In contrast, quantitative food web modeling showed that the composition of the plant community influenced nitrogen mineralization under individual plants, but that plant species identity did not affect nitrogen or carbon mineralization or food web stability. Hence, the composition and structure of entire soil food webs vary at the scale of individual plants and are strongly influenced by the species identity of the plant. However, the ecosystem functions these food webs provide are determined by the identity of the entire plant community.

Soil bacteria and protozoa affect root branching via effects on the auxin and cytokinin balance in plants - K. Krome; K. Rosenberg; C. Dickler; K. Kreuzer; J. Ludwig-Müller; C. Ullrich-Eberius; S. Scheu; M. Bonkowski (Plant and Soil, 2010)

Plant diversity effects on soil microorganisms support the singular hypothesis - N. Eisenhauer; H. Beßler; C. Engels; G. Gleixner; M. Habekost; A. Milcu; S. Partsch; A. C. W. Sabais; C. Scherber; S. Steinbeiss; A. Weigelt; W. W. Weisser; et al. (Ecology, 2010)
The global decline in biodiversity has generated concern over the consequences for ecosystem functioning and services. Although ecosystem functions driven by soil microorganisms such as plant productivity, decomposition, and nutrient cycling are of particular importance, interrelationships between plant diversity and soil microorganisms are poorly understood. We analyzed the response of soil microorganisms to variations in plant species richness (1–60) and plant functional group richness (1–4) in an experimental grassland system over a period of six years. Major abiotic and biotic factors were considered for exploring the mechanisms responsible for diversity effects. Further, microbial growth characteristics were assessed following the addition of macronutrients. Effects of plant diversity on soil microorganisms were most pronounced in the most diverse plant communities though differences only became established after a time lag of four years. Differences in microbial growth characteristics indicate successional changes from a disturbed (zymogeneous) to an established (autochthonous) microbial community four years after establishment of the experiment. Supporting the singular hypothesis for plant diversity, the results suggest that plant species are unique, each contributing to the functioning of the belowground system. The results reinforce the need for long‐term biodiversity experiments to fully appreciate consequences of current biodiversity loss for ecosystem functioning.

Earthworm and belowground competition effects on plant productivity in a plant diversity gradient - Nico Eisenhauer; Alexandru Milcu; Norma Nitschke; Alexander C. W. Sabais; Christoph Scherber; Stefan Scheu (Oecologia, 2009)

Zum Kurzzeitkriechverhalten von Warmarbeitsstählen - E. Stergar; M. Panzenböck; H. Leitner; H. Wurmbauer; C. Scheu; H. Clemens (BHM Berg- und Hüttenmännische Monatshefte, 2008)

Precipitates in a Fe-Co-Mo Alloy Characterized by Complementary Methods - E. Eidenberger; E. Stergar; H. Leitner; C. Scheu; P. Staron; H. Clemens (BHM Berg- und Hüttenmännische Monatshefte, 2008)

Influence of the Cooling Rate on the Mechanical Properties of a Hot-work Tool Steel - S. Mayer; C. Scheu; H. Leitner; H. Clemens; I. Siller (BHM Berg- und Hüttenmännische Monatshefte, 2007)